Kebijakan Pengelolaan Sumber Daya Alam di Indonsia pada Era Pemerintahan Jokowi: Tinjauan Ekonomi - Manihuruk, Frido Evindey; Alisya, Jeane; Syahbana, Eza; Purba, Bonaraja (STIE Jambatan Bulan, 2024)
This article is an economic review of government policies in the management of natural resources in Indonesia during the era of President Joko Widodo (Jokowi). Through a desk-based research method, it analyzes a series of policies implemented, such as the forest and plantation permit moratorium, forest restoration program, One Map initiative, Oil and Gas sector management, renewable energy development, and raw material export ban. From an economic perspective, this article evaluates the impact of these policies on economic growth, environmental resilience, and community welfare. The analysis identifies positive aspects and challenges in the implementation of natural resource management policies, and emphasizes the importance of striking the right balance between economic growth and environmental sustainability in formulating future policies